Effect of Low‐Density Lipoprotein Apheresis for Nephrotic Idiopathic Membranous Nephropathy as Initial Induction Therapy. Issue 6 (17th June 2019) - Koshi‐Ito, Eri; Koike, Kiyomi; Tanaka, Akihito; Watanabe, Yu; Kamegai, Naoki; Shimogushi, Hiroya; Shinjo, Hibiki; Otsuka, Yasuhiro; Inaguma, Daijo; Takeda, Asami
Abstract: Low‐density lipoprotein apheresis (LDL‐A) has been used for nephrotic syndrome (NS) caused by focal segmental glomerulosclerosis in Japan. Idiopathic membranous nephropathy (iMN) can also cause treatment‐resistant NS. Therefore, we investigated the effect of LDL‐A during initial induction for it. This retrospective, observational, and single‐center study enrolled consecutive iMN patients who received steroids from March 2000 to May 2015. We compared data between 11 patients treated with LDL‐A (LDL‐A group) and 27 patients without (non‐LDL‐A group) at baseline and 4 and 8 weeks later. Reduction rate of proteinuria and increase rate of serum albumin in LDL‐A group were significantly higher than the other after 4 weeks ( P = 0.036 and 0.030) and 8 weeks ( P = 0.030 and <0.001), respectively. There was no adverse event caused by LDL‐A and immunosuppressant dose was not significantly different. In conclusion, LDL‐A may be an effective choice for initial induction of nephrotic iMN.